Subcellular redistribution of trimeric G-proteins--potential mechanism of desensitization of hormone response: internalization, solubilization, down-regulation - Drastichová, Z; Bourová, L; Lisý, V; Hejnová, L; Rudajev, V; Stöhr, J; Durchánková, D; Ostasov, P; Teisinger, J; Soukup, T; Novotný, J; Svoboda, P (Physiological research, 2008)
Agonist-induced subcellular redistribution of G-protein coupled receptors (GPCR) and of trimeric guanine-nucleotide binding regulatory proteins (G-proteins) represent mechanisms of desensitization of hormone response, which have been studied in our laboratory since 1989. This review brings a short summary of these results and also presents information about related literature data covering at least small part of research carried out in this area. We have also mentioned sodium plus potassium dependent adenosine triphosphatase (Na, K-ATPase) and 3H-ouabain binding as useful reference standard of plasma membrane purity in the brain.
Keywords: Subcellular Fractions; Animals; subcelulární frakce; Sodium-Potassium-Exchanging ATPase; Brain; GTP-Binding Proteins; Cell Membrane; sodíko-draslíková ATPasa; Rats; Signal Transduction; hormony; heterotrimerní G-proteiny; proteiny vázající GTP; Cricetinae; Protein Multimerization; down regulace; multimerizace proteinu; mozek; Heterotrimeric GTP-Binding Proteins; zvířata; křečci praví; receptory spřažené s G-proteiny; Down-Regulation; Hormones; signální transdukce; Receptors, G-Protein-Coupled; buněčná membrána; krysa rodu Rattus